Penerapan Multimedia Interaktif untuk Meningkatkan Pemahaman Siswa terhadap Konsep IPAS Materi Makhluk Hidup di Kelas III Sekolah Dasar - Najwa Kayla A; Ibnu Muthi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the application of interactive multimedia in improving students' understanding of the concept of science and natural sciences on living things in grade III of elementary school. The method used is a literature study by analyzing various scientific journals, articles, and related documents. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that interactive multimedia makes a significant contribution in helping students understand abstract living things. This media presents information visually and verbally through images, sound, video, and animation, thereby increasing student involvement both cognitively and emotionally. The use of interactive multimedia also encourages active and scientific learning approaches such as observing, asking, and trying, which are in accordance with the cognitive development stage of elementary school students. Various studies have shown that the use of interactive multimedia improves learning outcomes by up to 25% compared to conventional methods. The main obstacle in its implementation is the limited facilities and ability of teachers to operate technology, but this can be overcome with training and support from various parties. In conclusion, interactive multimedia is effective as a learning aid to strengthen the understanding of science and natural sciences concepts, and is very relevant to the demands of 21st century learning which requires innovation, collaboration, and optimal use of technology in the classroom.